"Microplastic communities" in different environments: Differences, links, and role of diversity index in source analysis. (1st January 2021) - Li, Changchao; Gan, Yandong; Zhang, Chao; He, Huan; Fang, Jiaohui; Wang, Lifei; Wang, Yan; Liu, Jian
Highlights: The novel concept of "microplastic community" is introduced. Microplastic communities in different environments showed significant differences. Microplastic communities in environments were closely linked. The distance decay relationships for microplastics were significant. Diversity index MDII was established to reflect the number of microplastic sources. Abstract: Microplastics have been detected in various environments, yet the differences between microplastics in different environments are still largely unknown. Scientists have proposed the concept of the "microplastic cycle, " but the evidence for the movement of microplastics between different environments is still scarce. By screening the literature and extracting information, we obtained microplastic data from 709 sampling sites in freshwater, seawater, freshwater sediment, sea sediment, and soil in China. Based on the similarity between microplastics and biological communities, here we propose the concept of a "microplastic community" and examine the differences, links, and diversity of microplastic communities in different environments. Wilcoxon sign-ranks test, Kruskal-Wallis test, and analysis of similarities (ANOSIM) showed that there were significant differences in abundance, proportion of small microplastics, and community composition (shape, color, and polymer types) of microplastics in different environments. The Mantel test showed that there were significant correlations between microplastic community composition in different environments. Network analysis based on community similarity further confirmed the links between microplastic communities. The distance decay models revealed that the links weakened with the increase of geographic distance, suggesting that sampling sites with closed geographical locations had similar pollution sources and more easily to migrate or exchange microplastics. The microplastic diversity integrated index (MDII) was established based on the diversity of microplastic shape, color, and polymer types, and its indication of the number of microplastic pollution sources was verified by the statistical fitting relationship between the number of industrial pollution sources and MDII. Our study provides new insight into the differences and links between microplastics in different environments, which contributes to the microplastic risk assessment and demonstrates the "microplastic cycle." The establishment of the microplastic diversity integrated index could be used in source analysis of microplastics. Graphical Abstract: Image, graphical abstract